IEEE International Conference on Robotics and Automation, 2004. Proceedings. ICRA '04. 2004 2004
DOI: 10.1109/robot.2004.1307435
|View full text |Cite
|
Sign up to set email alerts
|

Development of a clinical jaw movement training robot for intermaxillary traction therapy

Abstract: We developed a jaw movement ,training robot system implementing a 6degee of free'dom (DOF) parallel mechanism, and applied it to jaw .opening and closing training, which is one of the therapies for temporomandibular joint disorders. A s one application of this system, we developed an intermaxillary traction therapy system that provides non-physiological movements, whereby the patients' jaws receive traction to regenerate healthy temporomandibular joint tissue. %is therapy is especially effective for patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, these are developed to act on the skin, rather than the facial tissues associated with oral disorders, meaning that they are ineffective for oral disorders. Takanobu et al (2003) and Okino et al (2004) developed opening jaw robots WY-5 and WY-6 and reported their effectiveness for people unable to open their mouths by themselves because of severe TMJ disorders. However, these robots are not effective for people in the first stages of TMJ disorders and dry mouth.…”
Section: Fig 1 Wao-1 (Waseda Asahi Oral-rehabilitation Robotmentioning
confidence: 99%
“…However, these are developed to act on the skin, rather than the facial tissues associated with oral disorders, meaning that they are ineffective for oral disorders. Takanobu et al (2003) and Okino et al (2004) developed opening jaw robots WY-5 and WY-6 and reported their effectiveness for people unable to open their mouths by themselves because of severe TMJ disorders. However, these robots are not effective for people in the first stages of TMJ disorders and dry mouth.…”
Section: Fig 1 Wao-1 (Waseda Asahi Oral-rehabilitation Robotmentioning
confidence: 99%
“…In order to determine the compliance position of the plunger, we used the virtual compliance control law defined as (1). As we may observe, the virtual compliance control is done by computing the actual position based on the reaction forces, assuming that a robot has virtual spring and damper elements [10]. Then, by using (2), the discrete value of x CC can be computed.…”
Section: Hemispherementioning
confidence: 99%
“…Work on robotic interfaces for facial rehabilitation is much more sparse, perhaps due to the relative difficulty in mechanically sensing facial movements. Representative in this area are the Waseda Yamanashi series of mouth opening and closing training robots, which feature manipulators that extend into the patient's mouth [32].…”
Section: Robotic Therapy and Playmentioning
confidence: 99%